Formation of Other Language Professional Communicative Competence of the Future Teachers of Foreign Languages by Means of Interactive Technologies - Yashchuk, Inna (Pedagogical Discourse, 2017)
The article deals with the practical aspect of the problem of formation of foreign language professional communication skills of the future foreign language teachers; interactive forms and methods of educational activity aimed at forming the specified qualities in students of pedagogical specialties like inside / outside circles, brain storm, think-pair-share, pair-in-interviews, jigsaw reading are indicated; the peculiarities of work with text for reading using multimedia resources (like on-line reading and off-line reading, audio reading, on the basis of which the phonetics of foreign language, its lexical basis, the basics of syntax and morphology, the skills of perception of speech by ear are worked out) are disclosed, which are aimed at developing critical thinking as a constructive intellectual activity, meaningful perception of information and its subsequent assimilation. The article reveals the essence of communicative tasks and exercises for reading, the essential characteristics of which are multi-functionality, problem orientation, situational, substantial fullness, complexity. In the article the characteristics of the professional position of the teacher-moderator and the function facilitization of high school teacher who works in the conditions of modernization of foreign language education are presented.